Objeción de conciencia sanitaria en España: naturaleza y ejercicio - Medina Castellano, Carmen Delia (2012)
Health conscientious objection in Spain: nature and exercise Conscientious objection is conceived as the infringement of a legal duty, peacefully and morally motivated, which aims to safeguard the own moral integrity against a heteronomous imperative judged as unfair. Generally, there is social agreement concerning some justice principles that generate group-shared laws. However, there can be disagreement among some of the members of the group, which can lead them to decide to break the law. The aim of this paper is to reflect on the social and juridical legitimacy of an individual’s moral obligation to disobey a rule that is incompatible with his or her personal options, in order to assert that faculty and base it on the existence of a conscientious objection right. Also, it seeks to point out the existing difficulties in Spain to exercise the conscientious objection within the healthcare sector.